Isolation of cDNA fragment encoding starch branching enzyme (Isoform) gene from metroxylon Sagu by rt pcr method - Tajuddin Sidek, Bin Hairaddin. (Universiti Malaysia Sarawak (UNIMAS), 2006)
Isolation and characterization of Starch Branching Enzyme (SBE) isoform I gene was the main objective of this study, where the target was to construct the cDNA from total RNA by using the specific primer that design manually. The RNA was extracted from plant that widely planted in muddy area that is sago palm (Metroxylon Sagu). In this study the extracted RNA was reverse-transcribed into cDNA in order to learn the property of the gene that responsible in starch synthesis that encodes for SBE isoform I. The RT PCR technique was used in this study to construct cDNA. Beside that, the comparison method also performs in order to compare which technique will generate cDNA easier. The comparison method that been used was RNase H treatment with the DNA polymerase I. The RNA was successfully extracted by the phenol extraction method with the DNase treatment. The construction of first strand also been achieved by using the RevertAid™ first strand cDNA synthesis kit. Constructions of second strand with the peR amplification and RNase H treatment were different method that can yield different quantity of cDNA. The cDNA was visualized under UV transilluminator to detect the present of cDNA from the sample.